Application Of Ginger Warm Compresses To Reduce Joint Pain: Case Study - Novri Andini; Dwi Cahya Rahmadiyah (Essential English Grammar, 2022)
Analysis of Nursing Care for for Mr.S’s Family with the Application of Ginger Warm Compress to Decrease Pain inDepok. Elderly has physiological changes that mostly occur is a decrease in musculoskeletal function including reducedmuscle strength, muscle mass, reduced bone mass, reduced fluids in the cells, so that erosion can occur on the jointsurfaces and cartilage covering the joint surfaces of damaged supporting bones, loss of cartilage, bone hypertrophy, andcapsule thickening. One of the manifestations of this change in the musculoskeletal system is chronic pain in joints cancause a negative impact for the elderly, such as disrupted daily activities and mobility. This case study aims to describethe results of interventions from non-pharmacological pain management, namely warm ginger compresses performed inthe elderly with chronic pain problems. Ginger warm compress is done eight times for 20 minutes in 3 weeks. The resultsof the intervention show that there is a decrease in pain scale by using the Visual Analog Scale (VAS) from moderate tomild pain. This shows that non-pharmacological pain management by applied warm ginger compresses can reduce painsymptoms. This study suggests the application of ginger warm compresses for the elderly with chronic pain in long-termcare institutions. Chronic pain in joints can cause a negative impact for the elderly, such as disrupted daily activities andmobility. This case study aims to describe the results of interventions from non-pharmacological pain management,namely warm ginger compresses performed in the elderly with chronic pain problems. Ginger warm compress is doneeight times for 20 minutes in 3 weeks. The results of the intervention show that there is a decrease in pain scale by usingthe Visual Analog Scale (VAS) from moderate (5-6 pain scale) to mild pain (1-2 pain scale) in the three managed families.This study shows that non-pharmacological pain management by applied warm ginger compresses can reduce painsymptoms. This study suggests the application of ginger warm compresses for the elderly with chronic pain in long-termcare institutions.